Pengaruh Struktur Aktiva, Likuiditas, Pertumbuhan Penjualan dan Risiko Bisnis terhadap Struktur Modal - Paramitha, Ni Nyoman; Wijana Asmara Putra, I Nyoman (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p04, 2020)
This study aims to determine the effect of asset structure, liquidity, sales growth and business risk on capital structure. This study took a sample of property and real estate companies listed on the Indonesia Stock Exchange in the period 2016-2018. The sample in this study was taken by the nonprobability sampling method using purposive sampling technique, so as many as 42 companies were obtained. The total sample taken for 3 years was 126 observations. The technique used in this research is multiple linear regression analysis. Based on the results of this research analysis proves that the structure of assets and sales growth has a positive effect on capital structure. Liquidity has a negative effect on capital structure. Business risk does not affect the capital structure. Keywords: Asset Structure; Liquidity; Sales Growth; Business Risk; Capital Structure.